Deep learning pedagogy to boost motivation and early numeracy–literacy in Indonesian early childhood education - Siti Hamidah; Ria Arista Asih; Ermanu Azizul Hakim; Nova Ariani (Universitas Muhammadiyah Malang, 2025)
Early-childhood education requires learning experiences that are emotionally engaging and contextually meaningful to support emergent literacy–numeracy. This study examines how Deep Learning (mindful, meaningful, and joyful learning) is implemented in a preschool setting and how it relates to children’s learning motivation and numeracy–literacy. A qualitative descriptive case study was conducted at TK ‘Aisyiyah II Banyuwangi, Indonesia, involving 20 children, two teachers, and one principal. Data were gathered through classroom observations, semi-structured interviews, and documentation and were analyzed using the Miles and Huberman interactive model (reduction–display–verification). Implementation through a Mini-Market Project was associated with stronger intrinsic motivation (enthusiasm, focus, independence) and observable gains in recognizing numbers/symbols, simple words, and money values within a playful and contextual environment. Teacher adaptability, institutional support, and parent collaboration emerged as key enabling factors. Deep Learning pedagogy is feasible for early-childhood classrooms and can strengthen motivation and emergent numeracy–literacy when embedded in authentic projects aligned with the Merdeka Curriculum and ESD-oriented learning goals.